Finance-dominated capitalism in Germany: Deep recession and quick recovery - Daniel Detzer; Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
Germany's recent export successes and the fast recovery from the 2007 -2009 crisis made it Europe's "economic superstar" in public opinion. This paper interprets the German performance against the background of financialisation. After an examination of the pre-crisis demand and growth regime, the focus is on how financialisation has contributed to the German 'export-led mercantilist' regime. The paper focuses subsequently on the determinants of the German current account balance, to then interpret the development of Germany during the financial and economic crisis and the causes for the quick recovery in light of the previous analysis.
Keywords: E25; E61; E63; E64; E65; F40; F43; 330; current account imbalances; financialisation; financial and economic crisis; Germany; trade balance